Validated screening tools to identify common mental disorders in perinatal and postpartum women in India: a systematic review and meta-analysis - Gracia Fellmeth; Siân Harrison; Charles Opondo; Manisha Nair; Jennifer J. Kurinczuk; Fiona Alderdice (BMC Psychiatry, 2021)
Abstract Background Perinatal common mental disorders are associated with significant adverse outcomes for women and their families, particularly in low- and middle-income settings. Early detection through screening with locally-validated tools can improve outcomes. Methods We searched MEDLINE, Embase, PsycINFO, Global Health, Cochrane Library, Web of Science and Google Scholar for articles on the validation of screening tools for common mental disorders in perinatal women in India, with no language or date restrictions. Quality was assessed using the QUADAS-2 tool. We used bivariate and hierarchical summary receiver operating characteristic models to calculate pooled summary estimates of sensitivity and specificity. Heterogeneity was assessed by visualising the distance of individual studies from the summary curve. Results Seven studies involving 1003 women were analysed. All studies assessed the validity of the Edinburgh Postnatal Depression Scale (EPDS) in identifying perinatal depression. No validation studies of any other screening tools were identified. Using a common threshold of ≥13 the EPDS had a pooled sensitivity and specificity of 88·9% (95%CI 77·4–94·9) and 93·4 (95%CI 81·5–97·8), respectively. Using optimal thresholds (range ≥ 9 to ≥13) the EPDS had a pooled sensitivity and specificity of 94·4% (95%CI 81·7–98·4) and 90·8 (95%CI 83·7–95·0), respectively. Conclusion The EPDS is psychometrically valid in diverse Indian settings and its use in routine maternity care could improve detection of perinatal depression. Further research is required to validate screening tools for other perinatal common mental disorders in India.